Bosentan added to sildenafil therapy in patients with pulmonary arterial hypertension - McLaughlin, Vallerie; Channick, Richard N; Ghofrani, Hossein-Ardeschir; Lemarié, Jean-Christophe; Naeije, Robert; Packer, Milton; Souza, Rogério; Tapson, Victor F; Tolson, Jonathan; Al Hiti, Hikmet; Meyer, Gisela; Hoeper, Marius M (The European respiratory journal, 2015)
The safety and efficacy of adding bosentan to sildenafil in pulmonary arterial hypertension (PAH) patients was investigated.In this prospective, double-blind, event-driven trial, symptomatic PAH patients receiving stable sildenafil (≥20 mg three times daily) for ≥3 months were randomised (1:1) to placebo or bosentan (125 mg twice daily). The composite primary end-point was the time to the first morbidity/mortality event, defined as all-cause death, hospitalisation for PAH worsening or intravenous prostanoid initiation, atrial septostomy, lung transplant, or PAH worsening. Secondary/exploratory end-points included change in 6-min walk distance and World Health Organization functional class at 16 weeks, change in N-terminal pro-brain natriuretic peptide (NT-proBNP) over time, and all-cause death.Overall, 334 PAH patients were randomised to placebo (n=175) or bosentan (n=159). A primary end-point event occurred in 51.4% of patients randomised to placebo and 42.8% to bosentan (hazard ratio 0.83, 97.31% CI 0.58-1.19; p=0.2508). The mean between-treatment difference in 6-min walk distance at 16 weeks was +21.8 m (95% CI +5.9-37.8 m; p=0.0106). Except for NT-proBNP, no difference was observed for any other end-point. The safety profile of bosentan added to sildenafil was consistent with the known bosentan safety profile.In COMPASS-2, adding bosentan to stable sildenafil therapy was not superior to sildenafil monotherapy in delaying the time to the first morbidity/mortality event.
Keywords: dospělí; Female; Hypertension, Pulmonary; Sildenafil Citrate; vazodilatancia; Adult; výsledek terapie; ženské pohlaví; Switzerland; Švýcarsko; lidé; dvojitá slepá metoda; Sulfonamides; Treatment Outcome; sildenafil citrát; Vasodilator Agents; prospektivní studie; Double-Blind Method; Male; Aged; Prospective Studies; sulfonamidy; kombinovaná farmakoterapie; plicní hypertenze; lidé středního věku; Antihypertensive Agents; senioři; mužské pohlaví; antihypertenziva; Middle Aged; Drug Therapy, Combination; Humans